El aseguramiento de la calidad como generador de cambios institucionales en universidades privadas de Colombia (2022)
The system for quality assurance of education in colombiahas been subject to several revisions and proposals regardingthe accreditation of higher education institutions and theundergraduate and postgraduate academic programs. Theseprocesses have been at the center of the discussion due to theirimpact on different areas of university institutions, such as academicdynamics, educational practices, organizational structures,government and university management, among others. In thiscontext, this article presents preliminary results of a research thataims to analyze the incidence of institutional accreditation inprivate universities of Bogotá and Medellín (during the period2015-2018), based on the methodological strategy of the casestudies. The bibliographic review and the interviews carried outallow us to identify processes and mechanisms related to quality that have been institutionalized, leading to internal changes, and that permeate different levels and actors within the institutions,while generating non-homogeneous effects and different answersaccording to the nature and identity of the institutions thatimplement them. that have been institutionalized, leading to internal changes, and